The influence of fly ash characteristics and reaction conditions on strength and structure of geopolymers. (30th September 2015) - Nikolić, Violeta; Komljenović, Miroslav; Baščarević, Zvezdana; Marjanović, Nataša; Miladinović, Zoran; Petrović, Rada
Highlights: Effects of FA characteristics and reaction conditions on geopolymer strength were studied. Development of FA-geopolymer structure was studied using SEM/EDS and NMR analyses. The correlation of FA characteristics, structure and strength of geopolymer was given. Strength of geopolymers was correlated with a fraction of Al-rich structural units. Rapid test for assessment of FA reactivity was evaluated. Abstract: Reactivity of Class F fly ash (FA), development of strength, and structure of FA-based geopolymers, depending on the reaction conditions, were examined in this paper. The results of SEM/EDS and NMR analyses revealed that the composition of aluminosilicate gel changed during reaction, i.e. Si/Al atomic ratio decreased with the reaction time. Higher strength of geopolymers was associated with a higher fraction of aluminum rich structural units, higher crosslinking, and more compact structure. A rapid test for the assessment of FA reactivity and thus the applicability of FA for geopolymer synthesis was proposed.